An unusual surgical cause of pyloric stenosis in an 8-month-old infant - Francis Msume Banda; M G Mutapanduwa; C Goutam; A Steenhoff; Dipesalema Joel (Wolters Kluwer Medknow Publications, 2017)
Infantile hypertrophic pyloric stenosis (IHPS) is the most common surgical cause of nonbilious, projectile vomiting in children. Its incidence is estimated to be 2-5/1000 live births and has been noted to be quite rare in African-Americans, Asians, and Indians. It is more common in infants under 6 months of age and is quite rare in older infants. While IHPS is invariably intrinsic in nature, extrinsic pyloric stenosis is very rare. Children who present with nonbilious, projectile vomiting after the age of 6 months should, therefore, be thoroughly investigated for causes other than IHPS. This is a case report of an 8-month-old child who had a band of tissue constricting the pylorus which mimicked IHPS.